Survival of Azospirillum brasilense in liquid formulation amended with different chemical additives - Reetha, G. Kumaresan *; D. (Journal of Phytology, 2011)
Liquid bioinoculant formulation has become the preferred technology to solve the problems associated with shorter shelf life, high contamination, poor quality, low field performance and processing solid carrier in carrier based bioinoculant formulation.Ã‚Â In this experiment, we evaluated different concentrations of six different chemical amendments viz, polyvinyl pyrollidone (PVP), glycerol, gum arabica, trehalose, polyethylene glycol (PEG) and polyvinyl alcohol (PVA) for their ability to support growth and promote survival of Azospirillum brasilense in N2 free malic acid broth during the storage. Some concentrations of various additives to N2 free malic acid broth promoted higher Azospirillum population compared to Azospirillum cells in N2-free malic acid broth alone. Liquid Azospirillum bioinoculant formulated with trehalose (10mM) promoted long term survival of Azospirillum followed by glycerol (10 mM) gum arabica (0.3%) and PVP (2%) and they supported 108 cells/ml up to 11 months of storage under ambient temperature (28Ã‚Â°C to 32Ã‚Â°C), whereas PEG (1%), PVA (0.5%) and control (lignite carrier) recorded the same population upto 8 months, 6 months and 5 months respectively. The results of the present study clearly indicated that the liquid formulation of Azospirillum could be used more effectively than the carrier based formulation.